An algorithm of converting business-process models into monochrome Petri nets on the basis of matrix formulas - M. G. Dorrer (Моделирование и анализ информационных систем, 2010)
A mechanism allowing the unique conversion of an event-based business process model of the ARIS EPC format into a monochrome Petri net is suggested. The Petri net ma¬trix representation resulting from this conversion allows investigating a business process topology and finding cycles and dead-ends. Moreover the Petri net matrix representation allows finding net invariants thus solving a task of finding all the business process development variants.